The relationship between estimated pulse wave velocity and 28-day mortality in patients with sA-AKI: a retrospective cohort analysis of the MIMIC-IV database - Lingchen Wei; Xinhai Cui; Yue Lv; Fan Zhang; Jianlin Wu (Renal Failure)
Background Acute kidney injury (AKI) is a common and serious complication in critically ill patients, especially those with sepsis. Recent studies suggest that estimated pulse wave velocity (ePWV) is an independent prognostic factor for in-hospital mortality in AKI patients. The objective of this research is to examine the correlation between ePWV and 28-day mortality among patients with sepsis-related acute kidney injury (SA-AKI).Methods This retrospective cohort study utilized data from 16,514 patients with SA-AKI in the MIMIC-IV database. ePWV was categorized based on the ROC curve cutoff value, dividing patients into two groups: high (>10.535 m/s) and low (≤10.535 m/s). To compare survival outcomes between the groups, Kaplan-Meier survival analysis was conducted. Cox proportional hazards models were used to assess the association between ePWV and 28-day mortality, adjusting for potential confounders. Additionally, a restricted cubic spline (RCS) model was employed to explore a possible dose-response relationship. Stratified analyses were conducted to examine the effect of ePWV on 28-day mortality across different subgroups.Results Survival analysis revealed that individuals with high ePWV experienced poorer 28-day survival outcomes compared to those with low ePWV. After adjusting for confounding factors, ePWV continued to be a predictive factor for 28-day mortality in patients with SA-AKI (p < 0.001). RCS model demonstrated a nonlinear association between ePWV and 28-day mortality (p for nonlinearity = 0.035).Conclusion ePWV serves as an independent predictor of 28-day mortality in patients with SA-AKI. This metric offers prognostic insights to help clinicians identify high-risk patients early, enabling timely interventions and better clinical outcomes.